Terapêutica Trombolítica no Enfarte Agudo do Miocárdio: Motivos de Inelegibilidade - Bentes de Jesus, M (1995)
STUDY OBJECTIVE: to establish the reasons of ineligibility for thrombolytic therapy (TL) in a group of patients with acute myocardial infarction (AMI). DESIGN: retrospective analysis of protocols and clinical records. SETTING: the medical intensive care unit (ICU) of a tertiary care hospital. PATIENTS AND METHODS: we studied the records from patients with AMI admitted to the ICU during a five-year period (1987-91) and excluded from TL, to determine the cause(s) of ineligibility. RESULTS: we found 1669 patients with AMI, 89 of which were excluded from the study. Of the remaining 1580 patients, 1274 (80.6%) did not receive TL. Mean age was 64.4 years; 66.4% were men. Mortality was 24.6%. Mean duration of chest pain was 19.4 hours. Chief reasons for exclusion from TL were advanced age (43.1% of patients) and delayed presentation (55.7%); one of these was present in 79.2%. CONCLUSIONS: this study confirmed the high mortality of patients with AMI who do not receive TL. Advanced age and delayed presentation were the main causes of ineligibility. As age is being abandoned as an exclusion criterion, efforts for expansion of TL should center on the earlier arrival of patients to centers where it is available.